2010
DOI: 10.1021/es101823z
|View full text |Cite
|
Sign up to set email alerts
|

Remote Identification and Quantification of Industrial Smokestack Effluents via Imaging Fourier-Transform Spectroscopy

Abstract: Industrial smokestack plume emissions were remotely measured with a midwave infrared (1800-3000 cm(-1)) imaging Fourier-transform spectrometer operating at moderate spatial (128 × 64 with 19.4 × 19.4 cm(2) per pixel) and high spectral (0.25 cm(-1)) resolution over a 20 min period. Strong emissions from CO(2), H(2)O, SO(2), NO, HCl, and CO were observed. A single-layer plume radiative transfer model was used to estimate temperature T and effluent column densities q(i) for each pixel's spectrum immediately above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 27 publications
(36 reference statements)
0
28
0
Order By: Relevance
“…Most scanning and imaging devices use UV radiation; however, spectrally resolved infrared radiation also has been used for characterizing the spatial distribution of industrial and volcanic emissions (Harig et al, 2005;Grutter et al, 2008b;Gross et al, 2010;Stremme et al, 2012a).…”
Section: A Krueger Et Al: Thermal Emission Spectroscopy Of Volcanicmentioning
confidence: 99%
“…Most scanning and imaging devices use UV radiation; however, spectrally resolved infrared radiation also has been used for characterizing the spatial distribution of industrial and volcanic emissions (Harig et al, 2005;Grutter et al, 2008b;Gross et al, 2010;Stremme et al, 2012a).…”
Section: A Krueger Et Al: Thermal Emission Spectroscopy Of Volcanicmentioning
confidence: 99%
“…Therefore, it can be shown that this eigen value equals (14) which is yielding the following optimal matched filter (15)…”
Section: B Matched Filtermentioning
confidence: 99%
“…in are combustion eciency estimations [23]. A single-layer radiative transfer model is also adequate for quantifying smokestack euent gases from coal-burning power facilities [24]. Fig.…”
Section: Introductionmentioning
confidence: 99%